mGlu5 receptors regulate synaptic sumoylation via a transient PKC-dependent diffusional trapping of Ubc9 into spines - Loriol, Céline; Cassé, Frédéric; Khayachi, Anouar; Poupon, Gwénola; Chafai, Magda; Deval, Emmanuel; Gwizdek, Carole; Martin, Stéphane (Nature communications, 2014)
Sumoylation plays important roles in the modulation of protein function, neurotransmission and plasticity, but the mechanisms regulating this post-translational system in neurons remain largely unknown. Here we demonstrate that the synaptic diffusion of Ubc9, the sole conjugating enzyme of the sumoylation pathway, is regulated by synaptic activity. We use restricted photobleaching/photoconversion of individual hippocampal spines to measure the diffusion properties of Ubc9 and show that it is regulated through an mGlu5R-dependent signalling pathway. Increasing synaptic activity with a GABA A receptor antagonist or directly activating mGlu5R increases the synaptic residency time of Ubc9 via a Gα q /PLC/Ca 2+ /PKC cascade. This activation promotes a transient synaptic trapping of Ubc9 through a PKC phosphorylation-dependent increase of Ubc9 recognition to phosphorylated substrates and consequently leads to the modulation of synaptic sumoylation. Our data demonstrate that Ubc9 diffusion is subject to activity-dependent regulatory processes and provide a mechanism for the dynamic changes in sumoylation occurring during synaptic transmission. Sumoylation plays key roles in neurotransmission but the mechanisms regulating this post-translational system in neurons remain unclear. Here the authors show that synaptic diffusion of the sole SUMO-conjugating enzyme Ubc9 is regulated by synaptic activity via an mGlu5R-dependent signalling pathway.